The nervous system of the most complex lophophore provides new insights into the evolution of Brachiopoda - Elena N. Temereva (Nature Portfolio, 2021)
Abstract The lophophore is a tentacle organ unique to the lophophorates. Recent research has revealed that the organization of the nervous and muscular systems of the lophophore is similar in phoronids, brachiopods, and bryozoans. At the same time, the evolution of the lophophore in certain lophophorates is still being debated. Innervation of the adult lophophore has been studied by immunocytochemistry and confocal laser scanning microscopy for only two brachiopod species belonging to two subphyla: Linguliformea and Rhynchonelliformea. Species from both groups have the spirolophe, which is the most common type of the lophophore among brachiopods. In this study, we used transmission electron microscopy, immunocytochemistry, and confocal laser scanning microscopy to describe the innervation of the most complex lophophore (the plectolophe) of the rhynchonelliform species Coptothyris grayi. The C. grayi lophophore (the plectolophe) is innervated by three brachial nerves: the main, second accessory, and lower. Thus, the plectolophe lacks the accessory brachial nerve, which is typically present in other studied brachiopods. All C. grayi brachial nerves contain two types of perikarya. Because the accessory nerve is absent, the cross nerves, which pass into the connective tissue, have a complex morphology: each nerve consists of two ascending and one descending branches. The outer and inner tentacles are innervated by several groups of neurite bundles: one frontal, two lateral, two abfrontal, and two latero-abfrontal (the latter is present in only the outer tentacles). Tentacle nerves originate from the second accessory and lower brachial nerves. The inner and outer tentacles are also innervated by numerous peritoneal neurites, which exhibit acetylated alpha-tubulin-like immunoreactivity. The nervous system of the lophophore of C. grayi manifests several evolutionary trends. On the one hand, it has undergone simplification, i.e., the absence of the accessory brachial nerve, which is apparently correlated with a reduction in the complexity of the lophophore’s musculature. On the other hand, C. grayi has a prominent second accessory nerve, which contains large groups of frontal perikarya, and also has additional nerves extending from the both ganglia to the medial arm; these features are consistent with the complex morphology of the C. grayi plectolophe. In brachiopods, the evolution of the lophophore nervous system apparently involved two main modifications. The first modification was the appearance and further strengthening of the second accessory brachial nerve, which apparently arose because of the formation of a double row of tentacles instead of the single row of the brachiopod ancestor. The second modification was the partial or complete reduction of some brachial nerves, which was correlated with the reduced complexity of the lophophore musculature and the appearance of skeletal structures that support the lophophore.